Negative Effects of High Glucose Exposure in Human Gonadotropin-Releasing Hormone Neurons - Annamaria Morelli; Paolo Comeglio; Erica Sarchielli; Ilaria Cellai; Linda Vignozzi; Gabriella B. Vannelli; Mario Maggi (International Journal of Endocrinology)
Metabolic disorders are often associated with male hypogonadotropic hypogonadism, suggesting that hypothalamic defects involving GnRH neurons may impair the reproductive function. Among metabolic factors hyperglycemia has been implicated in the control of the reproductive axis at central level, both in humans and in animal models. To date, little is known about the direct effects of pathological high glucose concentrations on human GnRH neurons. In this study, we investigated the high glucose effects in the human GnRH-secreting FNC-B4 cells. Gene expression profiling by qRT-PCR, confirmed that FNC-B4 cells express GnRH and several genes relevant for GnRH neuron function (KISS1R, KISS1, sex steroid and leptin receptors, FGFR1, neuropilin 2, and semaphorins), along with glucose transporters (GLUT1, GLUT3, and GLUT4). High glucose exposure (22 mM; 40 mM) significantly reduced gene and protein expression of GnRH, KISS1R, KISS1, and leptin receptor, as compared to normal glucose (5 mM). Consistent with previous studies, leptin treatment significantly induced GnRH mRNA expression at 5 mM glucose, but not in the presence of high glucose concentrations. In conclusion, our findings demonstrate a deleterious direct contribution of high glucose on human GnRH neurons, thus providing new insights into pathogenic mechanisms linking metabolic disorders to reproductive dysfunctions.